2009
DOI: 10.1128/jvi.02008-08
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Pattern Recognition Receptor-Mediated Innate Immunity Inhibits the Replication of Hepatitis B Virus in Human Hepatocyte-Derived Cells

Abstract: Recognition of virus infections by pattern recognition receptors (PRRs),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 84 publications
3
98
0
1
Order By: Relevance
“…Recent work has demonstrated that an overexpression of the TLR adapters MyD88 or TRIF, or an overexpression of the RIG-I and MDA5 adapters, inhibits HBV replication in HepG2 and Huh7 cells, suggesting that HBV is sensitive to PRR-mediated IFN signaling and the cellular antiviral response. 29 Our observation that HBx is an inhibitor of virus-triggered induction of type I IFNs provides a mechanistic explanation for the observation that HBV fails to induce type I IFNs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recent work has demonstrated that an overexpression of the TLR adapters MyD88 or TRIF, or an overexpression of the RIG-I and MDA5 adapters, inhibits HBV replication in HepG2 and Huh7 cells, suggesting that HBV is sensitive to PRR-mediated IFN signaling and the cellular antiviral response. 29 Our observation that HBx is an inhibitor of virus-triggered induction of type I IFNs provides a mechanistic explanation for the observation that HBV fails to induce type I IFNs.…”
Section: Discussionmentioning
confidence: 74%
“…26 Recently, several groups demonstrated that forced induction of type I IFNs by the overexpression of TLR or RLR signaling components inhibits HBV replication in the following experimental systems: in vivo, 27 in mice non-parenchymal cells 28 and in HepG2 and Huh7 cells. 29 The Wu group also determined that Toll-like receptors mediate IRF3 and IFN-b activation and can be inhibited by a high level of HBV replication in HBV-Met cells. 30 These results suggest that HBV has evolved mechanisms to overcome the innate immune response of the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…To date, limited information is available regarding which HBV components stimulate relevant PAMP receptors. In general, activation of TLR-dependent pathways suppresses HBV replication both in vitro and in vivo [22].…”
Section: Pattern Recognition Receptors In Hbv Infectionmentioning
confidence: 99%
“…Although the activation of the innate immune response has a key role in initiating the adaptive immune response, experimental results of HBV infection in both chimpanzees and woodchucks demonstrated non-or limited activation of innate immunity in acute HBV infection. 5,6 A number of recent studies [7][8][9][10] have investigated and suggested the involvement of innate cells, such as nature killer and nature killer T cells, in chronic HBV infection and suggested that these cells could play a role in liver damage during reactivation. Nevertheless, the role of innate immunity in viral clearance during HBV infection is still not clear.…”
Section: Introductionmentioning
confidence: 99%